Peran Pendidikan Islam Keluarga dalam Membentuk Praktik Hukum Keluarga Islam yang Responsif terhadap Hak Anak dan Perempuan: Pendidikan Islam Keluarga sebagai Fondasi Kesadaran Hak Anak dan Perempuan, Pendidikan Islam Keluarga dalam Mencegah Praktik Diskriminatif dan Kekerasan - Yoga Adhitya Fredy Firmansyah; Priska Wardina Putri; Moh. Faizin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This paper examines Islamic education within the domestic environment as a fundamental basis for developing an understanding of the rights of children and women within the framework of Islamic family law. This discussion positions the family as the primary educational institution, which plays a vital role in instilling the values of tawhid, ethics, and humanity, thereby fostering balanced and civilised relationships. This study employs a qualitative, legal-normative method through a literature review, analysing the concept of Islamic family education from theological, social, and legal perspectives. The research findings indicate that upbringing based on monotheism, the value of compassion (rahmah), the principle of justice (‘adl), and parental example form the primary foundation for building an understanding of the rights of children and women. Parents function as primary educators (murabbi) who not only nurture aspects of faith and moral character but also foster educational interactions that are empathetic and uphold humanistic values. Furthermore, Islamic family education serves a preventive function against unfair practices and aggressive behaviour within the household through the strengthening of egalitarian relationships, the enhancement of knowledge of family law based on gender equality, and the instilling of Islamic ethical values in communication. This study also emphasises that family education grounded in the maqāṣid al-syarī‘ah plays a role in protecting human life and dignity and breaking the cycle of domestic violence. Thus, strengthening Islamic education within the family constitutes a strategic step in fostering legal awareness, safeguarding the rights of children and women, and creating harmonious and sustainable family and societal structures.